The effect of feeding a novel multistrain yeast fraction on European seabass (Dicentrachus labrax) intestinal health and growth performance. Issue 6 (7th February 2019) - Rawling, Mark D.; Pontefract, Nicola; Rodiles, Ana; Anagnostara, Ilektra; Leclercq, Eric; Schiavone, Marion; Castex, Mathieu; Merrifield, Daniel L.
Abstract : Fish were fed a single‐strain yeast fraction (SsYF; 2 g/kg) or a multistrain yeast fraction (MsYF; 0.8 g/kg) for 10 weeks. The results demonstrated significant ( p  ≤ 0.03) elevations in weight gain, specific growth rate, protein efficiency ratio, and feed conversion ratio in fish fed the yeast fraction‐supplemented diets. In the distal intestine, a significant elevation in microvilli density was observed after 5 and 10 weeks of dietary supplementation with MsYF and SsYF, respectively, compared to control fed fish ( p  < 0.001). A significant elevation ( p  = 0.02) in the perimeter ratio was observed in fish fed diets supplemented with the yeast fractions. After 10 weeks of feeding on the experimental diets, Rt‐qPCR demonstrated a significant downregulation ( p  < 0.05) in the stress response genes, heat‐shock protein 70 ( hsp70 ) and proliferating cell nuclear antigen ( pcna ), in fish fed diets supplemented with the yeast fractions. Significant ( p  < 0.05) elevations in interleukin 1‐beta ( il1β ) and interleukin‐10 ( il10 ) gene expression were observed in fish fed diets supplemented with the MsYF compared to the other dietary groups. These findings suggest that feeding an MsYF specifically at a lower incorporation rate < 1 g/kg, compared to a commercial SsYF at 2 g/kg, is effective in improving the intestinal health status and growth performance of European seabass.